CD28-signaling can be partially compensated in CD28-knockout mice but is essential for virus elimination in a murine model of multiple sclerosis - Hülskötter, Kirsten; Lühder, Fred; Leitzen, Eva; Flügel, Alexander; Baumgärtner, Wolfgang (Frontiers in Immunology, 2023)
The intracerebral infection of mice with Theiler’s murine encephalomyelitis virus (TMEV) represents a well-established animal model for multiple sclerosis (MS). Because CD28 is the main co-stimulatory molecule for the activation of T cells, we wanted to investigate its impact on the course of the virus infection as well as on a potential development of autoimmunity as seen in susceptible mouse strains for TMEV. In the present study, 5 weeks old mice on a C57BL/6 background with conventional or tamoxifen-induced, conditional CD28-knockout were infected intracerebrally with TMEV-BeAn. In the acute phase at 14 days post TMEV-infection (dpi), both CD28-knockout strains showed virus spread within the central nervous system (CNS) as an uncommon finding in C57BL/6 mice, accompanied by histopathological changes such as reduced microglial activation. In addition, the conditional, tamoxifen-induced CD28-knockout was associated with acute clinical deterioration and weight loss, which limited the observation period for this mouse strain to 14 dpi. In the chronic phase (42 and 147 dpi) of TMEV-infection, surprisingly only 33% of conventional CD28-knockout mice showed chronic TMEV-infection with loss of motor function concomitant with increased spinal cord inflammation, characterized by T- and B cell infiltration, microglial activation and astrogliosis at 33-42 dpi. Therefore, the clinical outcome largely depends on the time point of the CD28-knockout during development of the immune system. Whereas a fatal clinical outcome can already be observed in the early phase during TMEV-infection for conditional, tamoxifen-induced CD28-knockout mice, only one third of conventional CD28-knockout mice develop clinical symptoms later, accompanied by ongoing inflammation and an inability to clear the virus. However, the development of autoimmunity could not be observed in this C57BL/6 TMEV model irrespective of the time point of CD28 deletion.